SUSTAINING LOCAL WISDOM AND ISLAMIC VALUES: AN ANALYSIS OF THE MARPEGE-PEGE TRADITION IN THE ANGKOLA COMMUNITY - Efendi, Sufrin; Malini, Riem (Edukasi Islami : Jurnal Pendidikan Islam, 2025)
This study examines the preservation of local wisdom and Islamic values through the marpege-pege tradition in the Angkola community. Employing a qualitative case study approach, the research explores the meanings, functions, and transformations of this tradition within its socio-cultural and religious context. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that marpege-pege functions as a social institution that facilitates collective resource redistribution, strengthens social solidarity, and reinforces kinship networks. It embodies key Islamic values, including ta‘āwun (mutual assistance), ukhuwah (brotherhood), and ṣadaqah (charity), positioning it as both a cultural and religious practice. From a sociological perspective, the tradition represents a form of social capital that enhances community resilience in the face of economic and social challenges. However, modernization, urbanization, and shifting value orientations have contributed to changes in its implementation, including reduced participation and a tendency toward transactional practices. These transformations risk weakening its core values of sincerity and collective responsibility. This study argues that the sustainability of marpege-pege depends on its adaptive reinterpretation, ensuring its relevance in contemporary society while preserving its essential cultural and religious foundations. The research contributes to the broader discourse on the interaction between local traditions and Islamic values in shaping social cohesion and cultural continuity.